Value orientation of Barangay people towards rural living: implications to rural development - Manero, Leonora P. (1985)
Values are the elements of life prevailing in a society. They provide motivation and ground for choice. They shape and determine individual's and group's decision to like or dislike, favour or disfavour,change or not to change. Thus, knowing people's value orientation will guide planners, policy-makers, and change agents in the planning and implementation of responsive development programmes capable of evoking maximum affirmative public response. Conducted to 143 randomly sampled household heads from two barangays in North Cotabato, Philippines, using interview schedule, group discussions, informal interview and participant observation, the study aimed primarily at determining barangay people's value orientation towards rural living and its implications to rural development. Specifically, it investigated the association between the following sets of variables: value orientation and age, sex cosmopoliteness, mass media exposure, and group membership; value orientation and responsiveness to rural development programmes; and two different groups' rank-ordering according to importance of Rokeach's Terminal and Instrumental values.